Aqueous oxidation of coal-associated pyrite and standard pyrite mineral towards understanding the depyritization kinetics and acid formations - Angana Mahanta; Binud Attry; Binoy K. Saikia (International Journal of Coal Science & Technology)
Abstract In coal mining areas, the ambient atmospheric and aqueous oxidation of pyrite minerals (FeS2) associated with coal as well as the other accompanying strata is significant in understanding the extent of acid mine drainage (AMD), the cause of severe environmental pollution. Therefore, in this paper, the oxidation kinetics of the coal-associated pyrite (CAPy) present in a coal sample (TpHM1) has been studied via aqueous leaching depyritization experiments at variety of temperatures and time intervals without the incorporation of any oxidizer. The outcomes obtained are juxtaposed with the standard pyrite mineral (SPM) oxidation at the same experimental conditions. Also, the coal and SPM slurry residues and filtrates obtained after aqueous leaching at 25 °C and 90 °C for 0 h and 24 h, respectively, were extensively analyzed through high-resolution transmission electron microscopy (HR-TEM), Powder X-ray diffraction (P-XRD), and X-ray-photoelectron spectroscopy (XPS) for evaluation of the mineralogical composition and proportions of iron and sulfur components during progression of the oxidation reaction. Both the reactions obey pseudo first-order kinetics during pyrite (FeS2) oxidation but a significant difference in the experimentally found activation energies (E a) and rate constants (k) values of oxidation kinetics of both CAPy and SPM may be attributed to the varied geochemical compositions of the coal associated pyrite (CAPy). The rate constant for CAPy is much greater than that of SPM implying a higher Ea around 10.838 kJ/mol for SPM as compared to 1.941 kJ/mol for CAPy. The CAPy in coal (TpHM1) is more susceptible to atmospheric oxidation than that of SPM, leading to the formation of acid mine drainage with lower pH. In this paper, the pH values on the basis of stoichiometric pyrite oxidation reaction were calculated and compared with the pH values obtained after aqueous leaching of CAPy to interpret the extent of acid formation and pyrite dissolution. Hence, with the assistance of the current study, further studies on the effects of mineral impurities, whereabouts of pyrite minerals in coal seams, the significance of compositional differences in the CAPy, the effect of metal oxides, and the role of alkalinity producing neutralizing agents of coal in the oxidative dissolution process of pyrite can be investigated.